The Effectiveness of the Psychosocial-Literacy Learning Model on Improving Students’ Language and Critical Thinking Skills - Kustyarini Kustyarini (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The language and critical thinking skills of students in higher education still show significant weaknesses, especially in conveying ideas reflectively, logically, and communicatively. Conventional learning models with minimal social interaction and unresponsive to students’ affective needs are considered ineffective in answering these challenges. This study aims to test the effectiveness of the learning model based on the psychosocial-literacy approach in improving students’ language skills. This approach integrates the critical literacy dimension with social interaction and emotional dynamics in the learning process. The study employed a descriptive qualitative method, utilizing data collection techniques such as observation, in-depth interviews, and documentation involving students from the language education study program at a university in Indonesia. The study results show that the psychosocial-literacy model can encourage improving students’ language skills in narrative structure, argumentative expression, and sensitivity to the text’s social context. In addition, this approach also creates a more inclusive, reflective, and dialogical learning atmosphere. These findings reinforce the argument that learning that combines cognitive, affective, and social dimensions can produce a transformative learning process and empower students. Thus, this study recommends implementing the psychosocial-literacy model as an alternative learning strategy that is more relevant in answering higher education needs in the 21st century.